Improving Performance in Complex Surroundings: A Mixed Methods Evaluation of Two Hospital Strategies in the Netherlands - Erik Wackers; Simone Dulmen; Bart Berden; Jan Kremer; Niek Stadhouders; Patrick Jeurissen (Kerman University of Medical Sciences, 2023)
Background  Hospital strategies aimed at increasing quality of care and simultaneously reducing costs show potential to improve healthcare, but knowledge on real-world effectiveness is limited. In 2014, two Dutch hospitals introduced such quality-driven strategies. Our aim was to evaluate contexts, mechanisms, and outcomes of both strategies using multiple perspectives.Methods  We conducted a mixed methods evaluation. Four streams of data were collected and analysed: (1) semistructured interviewing of 62 stakeholders, such as medical doctors, nurses, managers, general practitioners (GPs), and consultants; (2) financial statements of both organisations and other hospitals in the Netherlands (counterfactual); (3) national database of quality indicators, and patient-reported experiences; and (4) existing material on strategy development and effects.Results  Both strategies resulted in a relative decrease in volume of care within the hospital, while quality of care has not been affected negatively. One hospital failed to cut operating costs sufficiently, resulting in declining profit margins. We identified six main mechanisms that impacted these outcomes: (1) Quality-improvement projects spur change and commitment; (2) increased coordination between hospital and primary care leads to substitution of care; (3) insufficient use of data and support hinder quality improvement; (4) scaling down hospital facilities is required to convert volume reductions to cost savings; (5) shared savings through global budgets lead to shared efforts between payer and hospital; and (6) financial security for physicians facilitates shift towards quality-driven care.Conclusion  This integrated analysis of mixed data sources demonstrated that the institution-wide nature of the strategies has induced a shift from a focus on production towards quality of care. Longer-term (financial) sustainability of hospital strategies aimed at decelerating production growth requires significant efforts in reducing fixed costs. This strategy poses financial risks for the hospital if operating costs are insufficiently reduced or if payer alignment is compromised.